Psychological Distress Among Resident and Nonresident Fathers: Findings From New Zealand's Who Are Today's Dads? Project. (February 2019) - Rusten, Nikolas F.; Peterson, Elizabeth R.; Underwood, Lisa; Verbiest, Marjolein E. A.; Waldie, Karen E.; Berry, Sarah; Carr, Polly Atatoa; Grant, Cameron; Pryor, Jan; Nicolson, Jan; Morton, Susan M. B.
When fathers live away from their children, taking an active paternal role may become challenging and can add to paternal psychological distress. In a large ( N = 3, 980) diverse cohort, we found that nonresident fathers are more likely to be psychologically distressed than resident fathers (27.4% vs. 15.2%) and more likely to report wanting a change in the level of involvement they have in their child's life (76.6% vs. 58.1%). Nonresident fathers were more likely to suffer economic hardship, unemployment, poor health, and have a depression and anxiety history ( p s < .001). However, the factors associated with increased psychological distress were largely the same across resident and nonresident fathers. The biggest stressors were managing work alongside family responsibilities and commitments, arguments with the partner, prior history of depression, and economic hardship or deprivation. Fathers' actual levels of involvement and desired levels of involvement with their child did not predict their psychological distress.